EVALUATION OF THE KERATOMETRIC, BIOMETRIC DATA AND THE BIOMETRIC DEPENDENCIES AS RISK FACTORS OF REFRACTIVE ERROR IN IOL POWER CALCULATION - Gergana Popova; Latchezar Voynov (Peytchinski Publishing, 2019)
Purpose: The aim of the study is to evaluate the keratometric and biometric data and the biometric dependencies as risk factors of absolute refractive error (AE) in IOL power calculation of monofocal lenses in cataract patients using immersion ultrasound biometry (US-BM) and third generation formulas - SRK-T, Holl-1, Hoff-Q. Methods: We present a retrospective, case-control study. Two hundred and fifteen eyes of 158 patients with cataract are included that underwent uncomplicated phacoemulsification with implantation of monofocal IOL. Automated keratometry (Potec - 700), immersion ultrasound biometry (US-BM) and third generation formulas-SRK-T, Holladay-1, Hoffer-Q were used. Correlation analysis was performed between ocular keratometry and biometry values and the absolute error. Results: The predicted postoperative refraction (SE) in 137 eyes (63.7%) was successfully achieved with AE ± 0.50D. On the second visit after phacoemulsification (1-st month), 133 eyes (61.9%) had uncorrected distant visual acuity UCDVA ≥ 0.8.In our study was found that the keratometry procedure (KER) and surgically-induced astigmatism (SIA) were not sources of refractive error. Groups with larger relative shares of AE> ± 0.50D are with cylinder value prior to phacoemulsification (befCylD) > -0.75D, longer axial lenght (AL > 26.00 mm), shallower anterior chamber (ACD < 2.6 mm), smaller anterior segment (ACD + LT) <6.6 mm), smaller ratio of the anterior segment to the axial length (ACD+ LT / AL < 0.30). A methodology for estimating the expected AE has been proposed. Conclusion: The expected AE can be predicted via two preoperative factors: befCylD and the ratio of the anterior segment to the axial length (ACD + LT)/AL.